DIE SAW SE ROL IN SWA - Militaria, Editorial Team (Scientia Militaria - South African Journal of Military Studies, 2012)
Apart from the fact that the assistance of the SADF is necessary in many fields in SWA, such as public services and the medical and agricultural fields, it’s presence also serves another very important purpose. For as long as the Cubans are present in Angola, the SADF cannot withdraw. The Cubans exercise neo-colonialism in Angola and the moment the SADF withdraws from SWA this will create a void enabling the Cuban Forces to advance towards the South.